An expedition of Henry II, King of Germany, to the domain of Bolesław I the Brave in 1005 in the light of written sources and historical re-enactment - Danielewski, Marcin (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2022)
The article explores an expedition of Henry II, king of Germany, to the domain of Bolesław the Brave in 1005. While the issue has raised considerable interest in academic literature, the analyses have been carried out mainly in the context of major events i.e. the wars of 1002-1005, 1007-1013 and 1015-1018. In this work, an attempt has been made to narrow down the perspective to Henry II’s expedition of 1005 which reached as far as Poznań. To this end, I have analysed the written sources (specifically the records of Thietmar of Merseburg, a German chronicler) in an effort to indicate not only the expedition’s itinerary but also its rate and the state of preparation of the two major parties of the conflict, the German Reich and the Piast dominion. In addition, I have decided to make use of my experience of historical re-enactment in a pioneering way, in order to find out if the rate of the marching maintained by contemporary re-enactors of historical events provides a good comparison background for the rate of Henry II’s expedition of 1005. Next, archaeological sources provided some supplementary information on the conflict of 1005. In the light of all these data I have managed to adopt a different and unique approach to the analysed issue.